Lipoprotein Glycosylation by Protein-O-Mannosyltransferase (MAB_1122c) Contributes to Low Cell Envelope Permeability and Antibiotic Resistance of Mycobacterium abscessus - Becker, Katja; Haldimann, Klara; Selchow, Petra; Reinau, Lukas M.; Dal Molin, Michael; Sander, Peter (Frontiers in Microbiology, 2017)
Lipoproteins are important components of the mycobacterial cell envelope due to their function in cell wall homeostasis and bacterial virulence. They are posttranslationally modified with lipid- and glycosyl-residues in various species and interference with acylation or glycosylation leads to reduced growth and attenuated virulence in Mycobacterium tuberculosis. Lipoproteins are also expressed in the emerging and highly drug resistant pathogen Mycobacterium abscessus which frequently affects the lungs of patients with chronic pulmonary disease or cystic fibrosis. We investigated posttranslational modification, acylation and glycosylation, of heterologously expressed (M. tuberculosis LppX and Mpt83) and endogenous (SodC) lipoproteins at the molecular level in M. abscessus and identified MAB_1122c as protein O-mannosyltransferase (Pmt). Both, heterologous and endogenous lipoproteins carried a characteristic lipid anchor with palmitic acid (C16), palmitoleic acid (C16:1), oleic acid (C18) or tuberculostearic acid (C19) modifications. Multiple hexose-moieties were detected in the N-terminal region of the model lipoproteins expressed in M. abscessus. Conservation of lipoprotein glycosylation in M. tuberculosis and M. abscessus was revealed and points towards the existence of an O-glycosylation motif or other regulatory mechanisms regarding this posttranslational modification. Deletion of MAB_1122c prevented glycosylation and affected susceptibility to specific antibiotics which are large or target peptidoglycan synthesis and to lysozyme. Cell envelope permeability of M. abscessus ∆pmt was increased and mutant bacteria showed reduced survival inside macrophages. The results provide a link between posttranslational modification of lipoproteins and the permeability of the mycobacterial cell envelope which stresses the importance of lipoproteins as components of this complex structure.